The utility of two-dimensional real-time shear wave elastography for assessing liver fibrosis in patients with chronic hepatitis C virus infection. Issue 11 (November 2021) - Numao, Hiroshi; Shimaya, Koji; Kakuta, Akihisa; Shibutani, Koichi; Igarashi, Syohei; Hasui, Keisuke; Hanabata, Norihiro; Kanazawa, Kosuke; Munakata, Masaki
Abstract : Objective: Two-dimensional shear wave elastography (2D-SWE) is a new ultrasound-based elastography method to evaluate liver fibrosis in the daily practice. However, the utility of 2D-SWE among the other liver fibrosis markers is unclear. Methods: We enrolled 141 consecutive patients with hepatitis C virus infection, 66 men and 75 women (median age, 67 years), who underwent liver biopsy and 2D-SWE (LOGIQ E9, GE Healthcare, Wauwatosa, WI, USA). We compared the diagnostic accuracy of the 2D-SWE with those of magnetic resonance elastography (MRE; MR-Touch, GE Healthcare, Milwaukee, WI, USA), Mac-2 binding protein glycosylation isomer (M2BPGi), fibrosis-4 index (FIB-4) and platelet counts (PLT), using the histologic METAVIR scoring as the reference standard. Results: The areas under the receiver operating characteristics curves (AUROCs) of 2D-SWE, MRE, M2BPGi, FIB-4 and PLT for ≥F2, ≥F3 and F4 were 0.86, 0.88, 0.79, 0.81 and 0.77; 0.92, 0.93, 0.86, 0.87 and 0.83; and 0.91, 0.97, 0.85, 0.85 and 0.82, respectively. For diagnosing ≥F2 and ≥F3, the AUROCs of 2D-SWE and those of MRE showed no significant differences, and both 2D-SWE and MRE showed significantly higher AUROCs than the other markers. For diagnosing F4, the AUROC of MRE was significantly higher than those of other fibrosis markers. Conclusion: 2D-SWE has an excellent diagnostic accuracy equivalent to that of MRE for assessing significant (≥F2) and severe (≥F3) fibrosis. MRE demonstrated a higher AUROC than 2D-SWE, but this last one has advantages such as lower cost, fewer contraindications and greater ease of performance than MRE.